2015
DOI: 10.1109/jeds.2015.2390591
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel Field-Effect Transistors: Prospects and Challenges

Abstract: The tunnel field-effect transistor (TFET) is considered a future transistor option due to its steep-slope prospects and the resulting advantages in operating at low supply voltage (V DD ). In this paper, using atomistic quantum models that are in agreement with experimental TFET devices, we are reviewing TFETs prospects at L G = 13 nm node together with the main challenges and benefits of its implementation. Significant power savings at iso-performance to CMOS are shown for GaSb/InAs TFET, but only for perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
180
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(180 citation statements)
references
References 20 publications
0
180
0
Order By: Relevance
“…As the TFET current is dependent on the barrier shrinking in the sourcechannel interface, the resulting CGS is shown much lower than CGD when the transistor is active [13,14] The lower gate-capacitance of TFETs in comparison with Si MOSFETs can reduce the dynamic power consumption and delays of digital circuits as shown in [15]. In digital logic, the uni-directional conduction of TFET devices and the enhanced Miller capacitance can result in bootstrapped nodes within the circuit, causing potential failures and reliability risks [15,16]. In conventional MOSFETs , charges can be transferred under both positive and negative VDS bias due to a similar doping structure in the source and drain junctions.…”
Section: Tunnel Fet Intrinsic Capacitancementioning
confidence: 99%
See 1 more Smart Citation
“…As the TFET current is dependent on the barrier shrinking in the sourcechannel interface, the resulting CGS is shown much lower than CGD when the transistor is active [13,14] The lower gate-capacitance of TFETs in comparison with Si MOSFETs can reduce the dynamic power consumption and delays of digital circuits as shown in [15]. In digital logic, the uni-directional conduction of TFET devices and the enhanced Miller capacitance can result in bootstrapped nodes within the circuit, causing potential failures and reliability risks [15,16]. In conventional MOSFETs , charges can be transferred under both positive and negative VDS bias due to a similar doping structure in the source and drain junctions.…”
Section: Tunnel Fet Intrinsic Capacitancementioning
confidence: 99%
“…19, it is shown that despite the lower efficiency values at RF VAC values above 0.3 V, the FinFET-based GCCR presents the highest output voltage values. This characteristic is explained due to the higher current conducted by FinFETs at voltage values above 0.25 V when compared to heterojunction Tunnel FETs [15]. V. CONCLUSIONS In this work, the TFET device is explored as an alternative technology for front-end energy harvesting circuits as chargepumps and rectifiers.…”
mentioning
confidence: 99%
“…5,6) Therefore, narrower-bandgap materials have been intensively studied as TFET channel materials. [7][8][9][10][11][12][13] Among them, Ge is a unique and attractive material, [10][11][12][13] since it can be used as both n-and p-type MOS structure channels.…”
Section: Introductionmentioning
confidence: 99%
“…The use of different materials, device physics, and system architectures have been proposed to ensure continued performance improvement and energy efficiency. [1][2][3][4][5][6][7] Among these options, spintronic devices take advantage of the low switching energy of nanosized magnets, which theoretically can be switched with only a few tens of k B T per magnet. 8 Furthermore, since the information is processed in the form of magnetization, spin logic devices also possess memory storage capability that is nonvolatile, which could further reduce the power overhead.…”
mentioning
confidence: 99%